ショウワキチ アイスランド チジキ キョウエキテン チョウキ カンソク カラ エラレタ ELF/VLF ホウシャ ノ タイヨウ カツドウド イゾンセイ キセツ ヘンカ ヒヘンカ オヨビ シュウマツ コウカ - 山岸, 久雄; ヤマギシ, ヒサオ; 菊池, 雅行; キクチ, マサユキ; 佐藤, 夏雄; サトウ, ナツオ; 長野, 勇; ナガノ, イサム; Yamagishi, Hisao; Kikuchi, Masayuki; Sato, Natsuo; Nagano, Isamu; et al. (2002)
P(論文) 過去10数年にわたり南極昭和基地と, その地磁気共役点アイスランドで観測されたELF/VLF帯電磁放射データを解析し, 太陽活動度変化に関連する11年周期の変動を見出した。共役点での放射強度の日変化を比較すると, 磁気正午ではなく地方時の正午付近に最大値が現れる。これと夏半球で放射が強まる事実とを考え併せると, 日照の著しい電離層の下では, 地上電磁放射強度が高まることになる。750Hz帯電磁放射の日変化を, 週日と週末(土, 日)に別けて, 7年間の平均を求め, 比較したところ, 週日に比べ週末の放射強度が約8%低下することがわかった。これは産業社会の活動度が低下する週末には, 地上から磁気圏に洩れこむ電磁雑音レベルが低下し, その影響を受けて磁気圏電磁放射強度も低下するためと考えられる。 Long-term monitoring of natural radio wave emissions in the ELF/VLF range observed at Syowa Station, Antarctica (L=6.1) and its geomagnetic conjugate point in Iceland showed dependence on solar activities for solar cycles 21 and 22. It is also found that emissions were stronger in the summer hemisphere. Moreover, the daytime maximum of the emission appeared at local noon rather than magnetic noon. These two features indicate that the emissions observed on the ground intensified under the sunlit ionosphere. We also found a weekend decrease (-8%) of the emission intensity after 7 years of data average, suggesting that electromagnetic noises in the human world calm down on weekends, and this affected the efficiency of emission generation in the magnetosphere. departmental bulletin paper